Whole-exome sequencing for a rare case of aldosterone-producing adrenocortical carcinoma - WANG Hui-ping, CHANG Xiao-yan, MA Xiao-sen, TONG An-li (Jichu yixue yu linchuang, 2020)
Objective Aldosterone-producing adrenocortical carcinoma(ACC) is an uncommon disease.In this paper, the genetic mutations of aldosterone-producing ACC are studied by whole-exome sequencing. Methods Clinical data of the patient with aldosterone-producing ACC were collected. DNA was extracted from paraffin-embedded tissues and peripheral blood, then the whole-exome sequencing was carried out to identify germline and somatic mutations. Results There was no mutation associated with hereditary adrenocortical tumors and familial hyperaldosteronism in peripheral blood DNA. A total of 349 somatic mutations were found in tumor tissues, which were mainly enriched in tumorigenesis and calcium signaling pathways. Mutations related to the growth of adrenocortical tumor, CTNNB1, CDKN2A and MSH6, were detected, while no mutation related to aldosterone synthesis as KCNJ5, ATP1A1, ATP2B3 and CACNA1D was found in the tumor tissue. Conclusions The tumor- igenesis of aldosterone-producing ACC is related to CTNNB1, CDKN2A and MSH6, but the mechanism of promoting aldosterone production is still uncertain.